2003
DOI: 10.1016/s0014-5793(03)00509-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐angiogenic property of edible berry in a model of hemangioma

Abstract: Hemangiomas represent a powerful model to study in vivo angiogenesis. Monocyte chemotactic protein 1 (MCP-1) is known to be responsible for recruiting macrophages to sites of infection or in£ammation and facilitate angiogenesis. Recently we have demonstrated that edible berry extracts potently suppress inducible vascular endothelial growth factor expression and in vitro angiogenesis. Comparative analysis of several berry extracts led to the observation that wild blueberry and a berry mix were most e¡ective. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 50 publications
(58 reference statements)
2
45
0
1
Order By: Relevance
“…Hemangiomas represent a powerful model to study in vivo angiogenesis for the several reasons: the angiogenic process is extremely potent; the rapid proliferation hemangioma is associated with macrophage infiltration, indicating an important role for the microenvironment in angiogenesis; and hemangiomas are commonly encountered in humans, providing important clinical relevance. Inoculation with polyoma middle T-transformed endothelial cells is also considered as a good autocrine model of angiogenesis and hemangioma (31,32). We felt that using bEnd.3 cells to evaluate CCL2-induced angiogenesis manner would have several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Hemangiomas represent a powerful model to study in vivo angiogenesis for the several reasons: the angiogenic process is extremely potent; the rapid proliferation hemangioma is associated with macrophage infiltration, indicating an important role for the microenvironment in angiogenesis; and hemangiomas are commonly encountered in humans, providing important clinical relevance. Inoculation with polyoma middle T-transformed endothelial cells is also considered as a good autocrine model of angiogenesis and hemangioma (31,32). We felt that using bEnd.3 cells to evaluate CCL2-induced angiogenesis manner would have several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of anthocyanins has been shown to reduce the risk of coronary heart disease [Dell'Agli et al, 2004] and cancer [Hou, 2003]. Moreover, it has been reported that anthocyanins reduce the incidence of esophageal tumor [Kresty et al, 2001], reduce infiltration of macrophages in hemangioma [Atalay et al, 2003], and inhibit cell transformation [Xue et al, 2001], indicating potential cancer chemopreventive activity. While several studies indicate that anthocyanins exhibit strong scavenging of free radicals and antioxidant activities [Hou, 2003;Zheng and Wang, 2003], little is known about their antitumor activities.…”
mentioning
confidence: 99%
“…44 Interestingly, accumulation of myeloid cells (monocytes, macrophages, or dendritic cells) has been observed in infantile human hemangiomas 45,46 and in experimental hemangiomas. 47 In this latter model, inhibition of MCP-1 led to decreased infiltration of macrophages in hemangiomas and to diminished ability to form hemangiomas. 47 Our results confirm and extend these data by showing that N1 EC -expressing macrophages provide both pro-and anti-angiogenic signals.…”
Section: Macrophages Are Key Mediators Of Vascular Lesions Induced Bymentioning
confidence: 93%
“…47 In this latter model, inhibition of MCP-1 led to decreased infiltration of macrophages in hemangiomas and to diminished ability to form hemangiomas. 47 Our results confirm and extend these data by showing that N1 EC -expressing macrophages provide both pro-and anti-angiogenic signals.…”
Section: Macrophages Are Key Mediators Of Vascular Lesions Induced Bymentioning
confidence: 93%
See 1 more Smart Citation